Limb symmetry index on a functional test battery improves between one and five years after anterior cruciate ligament reconstruction, primarily due to worsening contralateral limb function. (July 2020) - Patterson, Brooke E.; Crossley, Kay M.; Perraton, Luke G.; Kumar, Avnish S.; King, Matthew G.; Heerey, Joshua J.; Barton, Christian J.; Culvenor, Adam G.
Abstract: Objective: Evaluate change in functional performance from 1- to 5-years after anterior cruciate ligament reconstruction (ACLR). Methods: 59 participants (38 men) aged 29 ± 16 years completed three hops and one-leg rise 1- and 5-years following ACLR. Linear mixed-effects models evaluated differences in change between the ACLR and contralateral limbs. Participants were classified with stable, improving or worsening function relative to previously published minimal detectable change thresholds. Healthy controls completed the three hops (n = 41) and one-leg rise (n = 31) as reference data. Results: The contralateral limb had a significantly greater decrease in functional performance between 1- and 5-years for the three hops, compared to the ACLR limb. Worsening was more common in the contralateral limb than the ACLR limb; resulting in significant improvements in the LSI for the single hop (mean 87% at 1-year to 95% at 5-years), side hop (77%to 86%) and one-leg rise (76% to85%). Performance of both ACLR and contralateral limbs and the LSI remained below the healthy controls. Conclusion: Functional performance changes differ between limbs between 1- and 5-years post-ACLR. The LSI should not be used in isolation to evaluate functional performance changes after ACLR, as it may overestimate functional improvement, due to worsening contralateral limb function. Highlights: The contralateral limb had a significantly greater decrease in function for the three hop tests compared to the ACLR limb. The LSI improved significantly for the single hop, side hop and one-leg rise between 1- and 5-years post-ACLR. The LSI overestimate improvement in functional ability following ACLR, due to worsening contralateral limb function. The LSI on all four tests at 1-year post-ACLR was significantly lower than healthy controls.